Pengaruh Globalisasi Ekonomi terhadap Inflasi: Pendekatan Data Panel - Nona Widharosa; Sri Andaiyani (Department of Development Economics, Universitas Sriwijaya, 2017)
There are similarities in views from economic researchers that globalization can have an impact on the behavior of domestic inflation. So that the characteristics of inflation which was initially only associated with domestic factors, became interesting to observe its relationship with economic globalization. Romer (1993) states that a more open country in the economy will have a lower inflation rate. This study aims to test the Romer hypothesis by analyzing the effect of the level of economic globalization on inflation in 102 countries during 1993 - 2013. The model specification test shows that the best method for this research data is the Fixed Effect Model (FEM). The results of the study concluded that there is a significant negative relationship between economic globalization and inflation